Manajemen Kepemimpinan Dalam Berbagai Kegiatan Managerial dan Keterampilan Kependidikan - joni putra; Suswanti Hendriani (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2023)
This research is to look at management leadership in various managerial and educational skills. Education is basically a conscious and planned effort to realize learning so that students have the skills that will be needed later in society. This type of research is a library research study. Literature review is an important part of a research that we do. The result of the research is that management is the process of coordinating work activities so that the work is completed efficiently and effectively. Managerial management is closely related to effective leadership management, because management is essentially a matter of interaction between good people